2015
DOI: 10.1155/2015/902982
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Technologies in Big Data Sensing: A Survey

Abstract: When the number of data generating sensors increases and the amount of sensing data grows to a scale that traditional methods cannot handle, big data methods are needed for sensing applications. However, big data is a fuzzy data science concept and there is no existing research architecture for it nor a generic application structure in the field of sensing. In this survey, we explore many scattered results that have been achieved by combining big data techniques with sensing and present our vision of big data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Crowd-sensing is an emerging paradigm that empowers users to provide data sensed or generated from their mobile devices (phones, wearables, etc.). It exploits the concept of human sensor to provide an insight on user behavior, improving observability of spaces and the way users interact with the indoor environment (Zhu et al 2015). Since energy consumption in buildings depends in great part on users' behavior (Erickson, Carreira-Perpiñán and Cerpa, 2014), crowd-sensing may support energy management by providing highly valuable information on occupancy, users' behavior and their interaction, but also give the users a possibility to express their needs.…”
Section: Acquisition Of Energy-related User Behavior Datamentioning
confidence: 99%
“…Crowd-sensing is an emerging paradigm that empowers users to provide data sensed or generated from their mobile devices (phones, wearables, etc.). It exploits the concept of human sensor to provide an insight on user behavior, improving observability of spaces and the way users interact with the indoor environment (Zhu et al 2015). Since energy consumption in buildings depends in great part on users' behavior (Erickson, Carreira-Perpiñán and Cerpa, 2014), crowd-sensing may support energy management by providing highly valuable information on occupancy, users' behavior and their interaction, but also give the users a possibility to express their needs.…”
Section: Acquisition Of Energy-related User Behavior Datamentioning
confidence: 99%
“…The services that may be performed by this layer include also the provision of a user interface through an IoT client device, to allow the user to interact with the IoT system [96]. This layer also includes data-mining algorithms [97,98].…”
Section: Iot Architecturementioning
confidence: 99%
“…For instance, Chen et al [3] propose a BECM system that keeps track of occupants' real-time location to enable fine-grained control of ambient environment including lighting, cooling, heating, etc. As sensors and actuators are deployed in buildings and these systems are connected to external networks such as the Internet, occupant security and privacy become a more challenging task since sensor data can be leveraged to make unwanted inferences about occupants and their behaviors [19]. For instance, Yang et al [17] have conducted empirical experiments using motion sensors in a three-person single-family home and electricity meters in a twelve-person university lab, and shown that data from these sensors can enable inferring real-time occupancy and even occupants' identities.…”
Section: Related Workmentioning
confidence: 99%